Hungary : Staff Report for the 2010 Article IV Consultation and Proposal for Post-Program Monitoring. (IMF Staff Country Reports; Country Report, 2011)
Hungary was severely affected by the crisis. The financial sector has remained resilient throughout the crisis. The Central Bank (MNB) paused in mid-2010 and has tightened interest rates by 50 basis points since November in response to a sharp rise in risk premia and higher headline inflation prints. The importance of addressing financial sector vulnerabilities is discussed. Executive Directors welcomed efforts to support distressed mortgage holders, as long as moral hazard and fiscal costs are contained. A medium-term framework was implemented.